Effect Of Variations in Pineapple (Ananas Comosus (L) Merr.) Extract On Physiochemistry and Sensory Characteristic Of Mozzarella Cheese - Muhammad Ardiyansyah; Kumala N.F.; Aulia M.; A.M. Handayani; Wahyu Suryaningsih; M. Mardiyanto; M.W. Apriliyanti (Journal of Food Industrial Technology, 2024)
Cheese is food processing from livestock with a white to yellowish color that was made from milk, enzyme rennet was used to coagulants. rennet enzyme more expensive than affordable other source coagulants like pineapple extracts that was contained bromelain enzyme to hydrolysis casein for made curd on processing mozzarella cheese. The aim of this research was effect of pineapple extract variations on the physicochemical properties such as hardness, water contents, and sensory properties of mozzarella cheese using a Completely Randomized Design (CRD) with 6 treatments and 3 replications. The results of the analysis of variance (ANOVA) of variations in pineapple extracts on hedonic and hedonic qualities properties such as texture, taste, and hardness have significantly. While, hedonic and hedonic qualities properties of color, aroma, and water contents have no significant influence. Thus, Better treatment was added by 30% pineapple extracts for mozzarella cheese which has hardness value of 22.883 mm/gr/sec, water contents of 41.74%, hedonic value of color=3.37 (like slightly), aroma=3.68 (like slightly), taste=3.96 (like) and texture 3.96(Like), hedonic quality value of color=3.32 (bone white slightly), aroma=3.84 (milk-flavour), taste=3 .92(savory) and texture 4.00 (elastic).